2nd World Congress on Sports Injury Prevention, 26-28 June, 2008, Tromsø, Norway (British Journal of Sports Medicine, 2008)
The aim of the World Congress on Sports Injury Prevention is to develop new concepts to enhance the safety in sports through a beneficial cooperation between scientists and practitioners. The program includes 81 international invited speakers from all over the world, providing a state-of-the-art multidisciplinary perspective on sports injury prevention. There is an exciting three-day program, including 5 keynote lectures and 19 3-hour or 90-minute symposia. In addition, the program includes 21 workshops, 52 oral presentations and 134 poster presentations from submitted abstracts.